Kajian Manajemen Mutu Perspektif Six Sigma pada Perusahaan Elsari Brownies dan Bakery Bogor - Muhammad Rizki; Wilson H. Limbong; Budi Suharjo (Institut Pertanian Bogor, 2011)
Quality Controlling (QC) has close relationship with technique and fabrication operational activities that aimed to monitor process and mitigate undesired result on quality series level that relevant to achieve economically outcome. QC was purposed to gain high quality product and homogenous that acceptable by the consumer and competitive with similar producer both at domestic and foreign level. Six sigma project management is one of a new breakthrough in solving organization problems and process management to support a company in increasing the product quality toward zero defects by means decreasing and preventing the same error. The research’s objectives are to study application of quality management from six sigma perspectives in Elsari Brownies & Bakery Company, Bogor. In particular, the research’s objectives are : (1) to study quality management system that applied by the company, (2) to measure production performance using six sigma concept on the company and (3) to formulate company’s strategy in increasing the quality of product. Data collection was carried out by direct observation on raw material supply process, production process and distribution, interview with company owner and head of production and also the consumer of Elsari Brownies & Bakery. The collected data are primary and secondary, that analyzed descriptively in order to give general description about controlling on production process that including on raw material supply, production process and the product. Furthermore, causal-effect diagram was used to describe significant relationship between effect and the cause. Causal factor was analyzed critically to determine the role on the effect. Causal effect diagram is powerful in determine the main factor that affect on quality fo final product. Quality management system in Elsari Brownies & Bakery Bogor was described as on raw material supply process, production process and product that selling to meet the quality standard. Six sigma project management with Define, Measure, Analyze, Improve and Control (DMAIC) method is possible to be implemented to improve production quality and quantity of brownies cake. The problem critical point (CTQ) in production process that can be identified is 3 (three) CTQ, namely ingredient, baking and cooling. After all, the problems level is measured and the causal was detected using the causal-effect diagram. Furthermore, the CTQ is improved, and controlling continuous implemented to maintain production quality and not repeated the error. According to measurement result using six sigma project management, the management has shows performance improvement therefore need to be maintain and improving. The improvement steps are including Standard Operating Procedur (SOP), information management, tools, and human resources quality improvement and lay out